Norwegian health personnel's compliance with new legislation on children of ill parents: an exploratory cross-sectional multicentre study - Kristin Stavnes; Torleif Ruud; Jūratė Šaltytė Benth; Ketil Hanssen-Bauer; Bente M. Weimand; Tytti Solantaus; Marit Hilsen; Bjørg Eva Skogøy; Ellen Katrine Kallander; Elin Kufås; Gro Christensen Peck; Bente Birkeland; et al. (BMC, 2022)
Abstract Background In 2010 the Norwegian Parliament introduced amendments to the Health Personnel Act requiring all health personnel to inform and offer help to their patients' children and families. We evaluated whether health personnel adhered to their obligations outlined in the Act and investigated whether family and health services characteristics were associated with the degree of compliance with the legislation. Our study was part of a larger Norwegian multi-site study conducted in five health trusts across Norway, assessing the situation for families living with parental illness. Method A cross-sectional study using quantitative data obtained from 518 patients 246 children and 278 health personnel was performed. All informants completed a questionnaire, including an instrument corresponding to the obligations in the legislation. Descriptive analyses, factor analysis and logistic regression analysis were used. Results The legislation was only partially implemented in the clinics of the health trusts. Compared to estimates prior to the introduction of the new legislation, the situation had improved somewhat, but much work remains to be done to fulfil the obligations decreed by law. The more time-consuming the obligations were, the less often they were met. The substance abuse and mental health services followed up on their obligations to a greater extent than did the physical health services. Conversely, children of physically ill parents were better informed by their families than were children of parents with mental health and substance abuse disorders. When asked the same questions, reports from health personnel were more positive compared to those of children and patients regarding the legislation's fulfillment. Conclusion Data suggest that there has been a change in the support offered to children of ill parents. Additional work is required, however, for the Health Personnel Act to function as fully intended.